The Impact of Brand Image and Marketing Mix on Buying Decision for Toyota Calya - Barkah Alkhaliq; Abdi R. Sastrawinata; Hijiri M. Aksani (International Journal of Engineering and Management Research, 2019)
Toyota Calya is one of Toyota’s product which succeed in achieving high sales volume based on GAIKINDO’s data. Toyota Calya sold around 68.038 unit for the year 2017 only. This fantastic sales volume record was indicated to be influenced by the strong brand image of Toyota in the mind of Indonesian consumers and the core elements which built Toyota Calya as a solid offering, includes product, price, place, and promotion. This research is designed to identify the impact of brand image and marketing mix variable on Toyota Calya’s buying decision. This quantitative research is conducted on 60 selected responders based on purposive sampling method. The method of analysis used in this research is multiple linear regression. The data analysis result shows that there is significant evidence to conclude that brand image and marketing mix variable has positive impact on Toyota Calya’s buiying decision. The well known Toyota brand and the easiness to gather relevan information about the product considered as strong contributor on Toyota Calya buying decision.